1991
DOI: 10.1177/002199839102500101
|View full text |Cite
|
Sign up to set email alerts
|

Damage Tolerance of Laminated Composites Containing an Open Hole and Subjected to Compressive Loadings: Part I—Analysis

Abstract: An analytical investigation was performed to study the damage in laminated composites containing an open hole and subjccted to compressive loading. A progressive damage model was developed during the inxstigation to predict the extent and the failure modes of the internal damage in the laminates as a function of the applied load and to simulate the in-plane response of the laminates from initial loading to final collapse. The model consists of a stress analysis and a failure analysis. Stresses and strains insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
152
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(162 citation statements)
references
References 44 publications
(27 reference statements)
9
152
0
1
Order By: Relevance
“…This difference is generally attributed to the thickness effect of the laminate, adjacent ply constraints and thermal residual stresses [Flaggs and Kural 1982;Peters 1984;Chang and Lessard 1991]. Here empirical relations proposed by [Chang and Lessard 1991] are adopted for calculating in situ ply strengths as a function of the laminate thickness and stacking sequence. These relations are given as…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…This difference is generally attributed to the thickness effect of the laminate, adjacent ply constraints and thermal residual stresses [Flaggs and Kural 1982;Peters 1984;Chang and Lessard 1991]. Here empirical relations proposed by [Chang and Lessard 1991] are adopted for calculating in situ ply strengths as a function of the laminate thickness and stacking sequence. These relations are given as…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The most commonly used failure criteria to predict pin joints failure are those based on Chang Chang [21] and Chang Lessard [22] formulations that consider only in plane stresses. Several studies has demonstrated that non linear shear stress strain relationship must be considered to predict pin joints bearing strength [23 26].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this work is the implementation of a new set of failure cri teria to predict bearing strength of bolted single lap composite joints. The proposed set of failure criteria is an extension of Chang Chang [21] and Chang Lessard [22] criteria including the effect of out of plane stresses.…”
Section: Introductionmentioning
confidence: 99%
“…However, their model results in underestimation of failure strength in some cases as pointed out by Icten and Karakuzu [2]. Chang and Lessard [3] extended the previous progressive damage model for investigating the compressive failure strength of laminated composites. Researchers like: Lessard and Shokrieh [4], Shahid and Chang [5], Su et al [6], Icten and Karakuzu [2] also studied damage accumulation in composite laminates.…”
Section: Introductionmentioning
confidence: 99%